Construction and evaluation of a prognostic model for cervical cancer based on dynamic hematological and clinical features - Huangrong Ma; Lingyu Ma; Li Yang; Miaoying Cai; Yifu Wang; Yue Li; Chunyu Liang; Zhiyuan Xu (BMC Cancer)
Abstract Objectives This study aims to investigate the prognostic significance of dynamic hematological and clinical characteristics and to construct nomograms to predict overall survival (OS) in patients with cervical carcinoma who underwent radical radiotherapy. Methods The study analyzed patients with cervical cancer who underwent radical radiotherapy at The University of Hong Kong-Shenzhen Hospital between January 2015 and June 2022 and were staged as IB1 to IVA according to the International Federation of Gynecology and Obstetrics (FIGO) 2018 staging system. We identified predictive factors through univariate and multivariate cox regression analyses. Two multivariate analyses integrating different groups of variables were conducted independently. Concordance index (C-index), receiver operating characteristic (ROC), and Kaplan-Meier curves were used to evaluate the nomograms. Bootstrap validation was performed to determine the accuracy of the nomogram using 1000 resamples. The performances of proposed nomograms and FIGO 2018 staging system were compared to assess the prognostic value of hematological and inflammatory markers. Results One hundred fifty-nine patients were included in this retrospective analysis. The median follow-up time was 41.37 months, and the 3-year OS rate was 82.6%. The first multivariate analysis of pre-treatment clinical factors and all hematological variables showed that FIGO2018 staging, and pre-treatment albumin levels were associated with 3-year OS. The final multivariate analysis incorporating all clinical factors, hematological variables, and inflammatory markers identified the following prognostic factors: FIGO2018 staging, rate of tumor shrinkage before brachytherapy, pre-treatment albumin levels, treatment times, minimum neutrophils during treatment, concurrent chemotherapy cycles, and lymphopenia grade. Calibration plots showed agreement between the OS predicted by the nomograms and actual OS. Kaplan–Meier curves demonstrated that patients in the high-risk group had shorter OS than those in the low-risk group (P ≤ 0.001). The C-index for the two nomograms was superior to that of the current FIGO2018 staging system, with values of 0.709 (95% Confidence Interval [CI], 0.622–0.795) and 0.803 (95% CI, 0.729–0.877), compared to 0.593 (95% CI, 0.508–0.678) for the FIGO system. Conclusion We developed and validated nomograms to predict OS in cervical cancer patients staged IB1 to IVA who underwent radical radiotherapy RT. The prognostic significance of dynamic changes in blood and inflammatory markers has been confirmed. The proposed nomogram exhibits robust predictive capabilities for estimating OS in these patients, facilitating risk stratification and individualized treatment.